Two new species of Sirindhornia from Vietnam (Lepidoptera: Tortricidae: Olethreutinae: Enarmoniini) - Heppner, John B.; Bae, Yang-Seop (Zootaxa, 2016)
Sirindhornia emmeli n. sp. and Sirindhornia ninhbinhensis n. sp. are described and illustrated from Vietnam (Tortricidae: Olethreutinae: Enarmoniini), and these are the first records of the genus from outside of Thailand.